2016
DOI: 10.1155/2016/1619053
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Phenotype of Inflammatory Bowel Disease

Abstract: It is widely known that there have been improvements in patient care and an increased incidence of Inflammatory Bowel Disease (IBD) worldwide in recent decades. However, less well known are the phenotypic changes that have occurred; these are discussed in this review. Namely, we discuss the emergence of obesity in patients with IBD, elderly onset disease, mortality rates, colorectal cancer risk, the burden of medications and comorbidities, and the improvement in surgical treatment with a decrease in surgical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 105 publications
(124 reference statements)
1
7
0
1
Order By: Relevance
“…The higher proportion of current and former smokers among those with Crohn's disease (37.2% of patients with Crohn's disease, 15.2% with ulcerative colitis, Table 1) further emphasizes the metabolic health needs of these patients. Modification of these cardiovascular disease (CVD) risk factors will potentially help to reduce the increased burden of CVD risk associated with rising age Dhingra and Vasan, 2012. Our findings are in keeping with the modern scenario of a patient with IBD, where undernutrition and underweight are becoming rarer and replaced by the malnutrition of obesity and the metabolic syndrome Bryant et al, 2013, Moran et al, 2016. This is at odds with the previous impression of a typical underweight IBD phenotype which may have been explained by reduced dietary intake, malabsorption, increased energy expenditure from inflammation and decreased respiratory quotient Dong et al, 2015.…”
Section: Discussionsupporting
confidence: 66%
“…The higher proportion of current and former smokers among those with Crohn's disease (37.2% of patients with Crohn's disease, 15.2% with ulcerative colitis, Table 1) further emphasizes the metabolic health needs of these patients. Modification of these cardiovascular disease (CVD) risk factors will potentially help to reduce the increased burden of CVD risk associated with rising age Dhingra and Vasan, 2012. Our findings are in keeping with the modern scenario of a patient with IBD, where undernutrition and underweight are becoming rarer and replaced by the malnutrition of obesity and the metabolic syndrome Bryant et al, 2013, Moran et al, 2016. This is at odds with the previous impression of a typical underweight IBD phenotype which may have been explained by reduced dietary intake, malabsorption, increased energy expenditure from inflammation and decreased respiratory quotient Dong et al, 2015.…”
Section: Discussionsupporting
confidence: 66%
“…However, Parra et al [ 30 ] found a predominance of ileocolonic location (53.0%) and penetrating phenotype (52.0%) in the SE region that was higher than that usually reported by European studies[ 33 ]. Other studies, including ones from Hungary, the Netherlands, Australia and Asia, reported proportions of ileocolonic disease ranging from 38.8% to 45%[ 34 ]. Parente et al [ 13 ] reported a frequency of colonic location of 36.0% and a frequency of nonstricturing/nonpenetrating disease of 69.0% in the Northeast region.…”
Section: Discussionmentioning
confidence: 99%
“…Although the phenotype of IBD is changing with the prevalence of obesity and overweight patients gradually rising [ 29 ], approximately one in six patients still suffer from significant malnutrition, often related to more severe forms of disease and accompanied by self-imposed food restriction behaviour [ 30 ]. Apart from the acknowledged influence of medication and bowel surgery, presence of NAFLD in underweight IBD patients could, furthermore, be an indicator of and independent and different pathophysiology, which is not associated with obesity or insulin resistance [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%